Relationship of job performance with organizational commitment components and job satisfaction among nurses in Hospital Universiti Sains Malaysia - Otoum, Rami Ahmad Yaqoup (2021)
In the light of the importance of the performance of nurses in health services, this study established to develop a model of job performance with organizational commitment components and job satisfaction among nurses at Hospital USM, Malaysia. Also, this study examines the mediation effect of job satisfaction between organizational commitment components and job performance among nurses. The study proposes that affective, normative, and continuance commitments have an influence on job performance through job satisfaction. Using the online survey method, 176 completed responses were collected from nurses. Pearson correlation was conducted to examine the association between study variables. A multiple linear regression was constructed to test the mediation effect of job satisfaction between organizational commitment and job performance and to analyse which variable contributes more to the job performance in order of developing the job performance model. The study results showed that all components of organizational commitment and job satisfaction are positively correlated to job performance (p < 0.05). In addition, job satisfaction has a positive association with organizational commitment components (p < 0.05). However, job satisfaction is found to mediate the relationship between affective commitment, normative commitment as well as continuance commitment and job performance. Furthermore, the results indicated that only normative commitment (B= 0.29, p < 0.05) and job satisfaction (B= 0.28, p < 0.05) contribute significantly to the job performance. Therefore, improving OC and JS among nurses could increase their performance. Nurses managers should create In the light of the importance of the performance of nurses in health services, this study established to develop a model of job performance with organizational commitment components and job satisfaction among nurses at Hospital USM, Malaysia. Also, this study examines the mediation effect of job satisfaction between organizational commitment components and job performance among nurses. The study proposes that affective, normative, and continuance commitments have an influence on job performance through job satisfaction. Using the online survey method, 176 completed responses were collected from nurses. Pearson correlation was conducted to examine the association between study variables. A multiple linear regression was constructed to test the mediation effect of job satisfaction between organizational commitment and job performance and to analyse which variable contributes more to the job performance in order of developing the job performance model. The study results showed that all components of organizational commitment and job satisfaction are positively correlated to job performance (p < 0.05). In addition, job satisfaction has a positive association with organizational commitment components (p < 0.05). However, job satisfaction is found to mediate the relationship between affective commitment, normative commitment as well as continuance commitment and job performance. Furthermore, the results indicated that only normative commitment (B= 0.29, p < 0.05) and job satisfaction (B= 0.28, p < 0.05) contribute significantly to the job performance. Therefore, improving OC and JS among nurses could increase their performance. Nurses managers should create